Ultra-deep sequencing mutation analysis of the BCR/ABL1 kinase domain in newly diagnosed chronic myeloid leukemia patients. (December 2021) - Park, Hyunkyung; Kim, Inho; Kim, Hyeong-Joon; Shin, Dong-Yeop; Lee, Sung-Yeoun; Kwon, Oh-Hyung; Kim, Dae-Young; Lee, Kyoo-Hyung; Ahn, Jae-Sook; Park, Jinny; Sohn, Sang-Kyun; Lee, Jeong-Ok; et al.
Highlights: Ultra-deep sequencing is a sensitive method for genetic-based treatment decisions. Specific mutations could have a prognostic application in predicting response. Based on mutational analyses, nilotinib is a promising option for Korean patients. Abstract: Ultra-deep sequencing detects low-frequency genetic mutations with high sensitivity. We used this approach to prospectively examine mutations in the BCR/ABL1 tyrosine kinase from patients with newly diagnosed, chronic-phase chronic myeloid leukemia ( CML) treated with the tyrosine kinase inhibitor nilotinib. Between May 2013 and November 2014, 50 patients from 18 institutions were enrolled in the study. We screened 103 somatic mutations and found that mutations in the P-loop domain were the most frequent (173/454 mutations in the P-loop) and noted the presence of the V299 L mutation (dasatinib-resistant/nilotinib-sensitive) in 98 % of patients (49/50). No patients had Y253H, E255 V, or F359 V/C/I mutations, which would recommend dasatinib rather than nilotinib treatment. The S417Y mutation was associated with lower achievement of a major molecular response (MMR) at 6 months, and the V371A mutation was associated with reduced MMR and MR 4.5 durations (MMR for 2 years: 100 % for no mutation vs. 75 % for mutation, P= 0.039; MR 4.5 for 15 months: 94.1 % vs. 25 %, P= 0.002). Patients with known nilotinib-resistant mutations had lower rates of MR 4.5 achievement. In conclusion, ultra-deep sequencing is a sensitive method for genetic-based treatment decisions. Based on the results of these mutational analyses, nilotinib treatment is a promising option for Korean patients with CML.